A Case of Ingested Laryngoscope Bulb During Emergency Endotracheal Intubation - Saurabh Sharma; Sandhya Gupta; Tushar Nagyan; Md Abu Nasar; Sowbir Some; P. N. Agarwal (Indonesian Journal of Medical Sciences and Public Health, 2021)
Laryngoscope is one of the most important lifesaving tools in the armamentarium of medical personnel. As is the case with any other tool, this too is susceptible to rare failures. One of these rare malfunctions is the dislodgement of bulb during endotracheal intubation. This can be associated with serious consequences if patient aspirates or ingests the bulb. In the following communication we report this off chance mishap while intubating a patient in trauma ICU.